Climatic changes, government interventions, and paddy production: an empirical study of the Muda irrigation area in Malaysia - Ibrahim, Ahmad Zubir; Alam, Md Mahmudul (Inderscience Enterprises Ltd., 2016)
The Muda irrigation area is one of the main paddy production areas in Malaysia.Various efforts and approaches through government interventions have been implemented to ensure the continuity of paddy production in this area.However, there are different factors that have negative impacts on paddy production including climatic factors. Therefore, with the direct components of production such as land, labour, and technology, this study uses climatic factors and government intervention to examine the influence of these factors of production on the paddy production in this area.Based on the time series data from 1981 to 2010, this study conducted the multiple log linear Ordinary Least Square (OLS) regression by considering the Cobb-Douglas production function model.The major units of production, such as land, labour, and technology, have a statistically positive relationship with paddy production.Among the climatic variables, rainfall and the number of rainy days show a statistically significant and positive relationship but temperature shows a negative relationship with paddy production.The factors of external intervention such as government subsidies and market forces also show a statistically significant and positive relationship with paddy production.To ensure the improvement of paddy production as well as to minimise the effects of climatic change, government intervention should be continued in Malaysia.